2014
DOI: 10.1007/s11655-014-1854-y
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical profiling and bioactivity of a mangrove plant, Sonneratia apetala, from Odisha Coast of India

Abstract: Sonneratia apetala extracts have potent antibacterial, antioxidant, antidiabetic and anticancer properties which can be further exploited for its pharmaceutical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 37 publications
0
25
0
3
Order By: Relevance
“…[39] Figure 2B showed a few unidentified peaks in the chromatogram because we used only nine phenolic standards to quantify them in the MS of S. apetala fruit. The unidentified peaks appeared in the regions which recognized the presence of simple polyphenols, catechins, anthocyanins, and flavonoid glycosides [40] in MS. Patra et al [15] reported catechol-like phenolic compounds in the methanol extracts of leaf and bark of S.…”
Section: Downloaded By [Mcmaster University] At 20:34 10 October 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…[39] Figure 2B showed a few unidentified peaks in the chromatogram because we used only nine phenolic standards to quantify them in the MS of S. apetala fruit. The unidentified peaks appeared in the regions which recognized the presence of simple polyphenols, catechins, anthocyanins, and flavonoid glycosides [40] in MS. Patra et al [15] reported catechol-like phenolic compounds in the methanol extracts of leaf and bark of S.…”
Section: Downloaded By [Mcmaster University] At 20:34 10 October 2015mentioning
confidence: 99%
“…Fruits and barks of the plants belonging to genus Sonneratia have remedial activities against asthma, febrifuge, ulcers, swellings, sprains, bleeding, hemorrhages and piles. [14] Patra et al [15] reported antibacterial, antioxidant, antidiabetic and anticancer activities of leaf and bark extracts of S. apetala. Nevertheless, a little scientific attention on the fruit has been paid till today.…”
Section: Introductionmentioning
confidence: 99%
“…Sonneratia apetala ( S. apetala ), also called Keora in local, is a member of the Lythraceae belonging to mangrove, which widely exists in Sundarbans (the world's largest mangrove forest) and the coastal regions in Bangladesh, India, Myanmar, Malaysia, New Guinea, China, etc. [10–12]. As an exotic mangrove species introduced from India, Bengal, and Sri Lanka [13], S. apetala mainly distributes in the southeast coastal areas in China [14] and serves as the dominant species of mangroves because of its high adaptability, rapid growth, high seed setting rate, and other characteristics [15].…”
Section: Introductionmentioning
confidence: 99%
“…Jaimini et al (2011) determined the antibacterial potential of S. apetala leave extracts. Also, Patra et al (2015) focused on both S. apetala leaf and bark extracts and they concluded that the extracts have potent antibacterial, antioxidant, antidiabetic and anticancer properties, which can be further explored for their pharmaceutical applications. After fractionation of S. apetala bark extract using Sep-pak plus cartridges, various bioactivities in the fractions were reported (Tan & Thuy, 2014).…”
Section: Sonneratia Apetala Buch Ham Was First Imported From Myanmarmentioning
confidence: 99%
“…S. apetala leaf extracts is known to have antibacterial activity against both gramnegative and gram-positive bacteria (Jaimini et al, 2011). Patra et al (2015) focused on the antibacterial activity of S. apetala, and suggested that methanol extracts of leaves and bark possess inhibition activity on all 9 and 7 (except E. coli and S. epidermidis) test species, respectively. We also reported previously that methanol extracts of leaves, fruit, bark, and pneumatophore of S. apetala by Soxhlet extractor showed antibacterial activity against E. coli (Tan et al, 2014).…”
Section: Antibacterial Activitymentioning
confidence: 99%